Collaborative Management Model for Bullying Prevention in Islamic Boarding Schools: A Multi-Stakeholder Approach - Mar'atul Azizah; Moch. Sya’roni Hasan; Mufarikha Binti Syarkun (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
Bullying in Islamic boarding schools (pesantren) presents unique challenges requiring culturally appropriate intervention strategies. This study examines the effectiveness of a collaborative management model involving kyais (Islamic scholars), ustadz (teachers), and administrators in bullying prevention at Pondok Pesantren Kalimasada Jombang, Indonesia. A qualitative case study was conducted over six months using purposive and snowball sampling. Data were collected from fifteen informants through in-depth interviews, participant observation, and document analysis. Data analysis employed Miles and Huberman's interactive model with triangulation. The collaborative management model demonstrated significant effectiveness through three integrated approaches: spiritual leadership by kyais, focusing on Islamic character building, operational implementation by ustadz through counseling and monitoring, and administrative coordination through policy development. The integration of restorative justice principles with Islamic values proved particularly effective in preventing bullying recurrence. Study limitations include a single-case design limiting generalizability and a six-month timeframe constraining long-term assessment. Practically, this model provides a replicable framework for Islamic educational institutions, offering specific role distribution guidelines while maintaining Islamic educational values. This Islamic-based collaborative approach offers a culturally appropriate alternative to conventional anti-bullying strategies.